Evidence of reduced birthweight in Ukraine following the Russian invasion - Svitlana Arbuzova; Margaryta Nikolenko; Liubov Atramentova; Howard Cuckle (Scientific Reports)
Abstract The impact of armed conflict on birth weight has been shown in various studies, but the effects of the full-scale Russian invasion of Ukraine in 2022 have been overlooked until now. This study investigates the influence of war on birth-weight using data and follow-up of pregnancies among women having prenatal screening. Maternal factors, outcomes, and birth weights were analyzed for 706 screened women who delivered between 2020 and 2023, excluding cases of spontaneous abortion, termination, and multiple pregnancies. Of these, 330 deliveries occurred before the invasion and 376 afterward. The only statistically significant maternal factors were parity − 22% nulliparous before and 48% after invasion (P < 0.0001) and maternal weight − 60 versus 62 kg. (P < 0.05). Birth-weight was significantly reduced: median 3500 g before and 3350 g after (P < 0.0001); proportions < 2500 g, 1.2% and 2.4%, respectively (P = 0.24). The ratio of birth-weight to infant length was also significant (P < 0.0001). Analysis of variance showed birth-weight significances remained after allowing for parity and gender. These findings highlight a significant decline in birth weight associated with armed conflict, emphasizing the need for targeted interventions to support maternal and neonatal health during periods of war.